Tropical Indian Ocean basin hydroclimate at the Mid- to Late-Holocene transition and the double drying hypothesis. (15th January 2023) - Scroxton, Nick; Burns, Stephen J.; McGee, David; Godfrey, Laurie R.; Ranivoharimanana, Lovasoa; Faina, Peterson; Tiger, Benjamin H.
Abstract: The spatial pattern of Holocene climate anomalies is crucial to determining the mechanisms of change, distinguishing between unforced and forced climate variability, and understanding potential impacts on past and future human societies. The 4.2 ka event is often regarded as one of the largest and best documented abrupt climate disturbances of the Holocene. Yet outside the data-rich Northern Hemisphere mid-latitudes, the global pattern of climate anomalies is uncertain. In this study we investigate the spatial and temporal variability of the tropical Indian Ocean hydroclimate at the Mid- to Late-Holocene transition. We conducted Monte-Carlo principal component analysis, considering full age uncertainty, on ten high-resolution, precisely dated paleohydroclimate records from around the tropical Indian Ocean basin, all growing continuously or almost continuously between 5 and 3 kyr BP. The results indicate the dominant mode of variability in the region was a drying between 3.97 kyr BP (±0.08 kyr standard error) and 3.76 kyr BP (±0.07 kyr standard error) with dry conditions lasting for an additional 300 years in some records, and a permanent change in others. This drying in PC1, which we interpret as a proxy of summer monsoon variability, fits with a previously recognised tropic wide change in hydroclimate around 4.0 kyr BP. An abrupt event from 4.2 to 3.9 kyr BP is seen locally in individual records but lacks regional coherence. A lack of apparent 4.2 ka event in tropical Indian Ocean hydroclimate has ramifications for climate variability in the Indus valley, and for the Harappan civilization. Through a comparison of existing Indian subcontinent paleoclimate records, upstream climatic variability in the Indian Summer Monsoon and winter Westerly Disturbances source regions, and modern climatology, we present the "Double Drying hypothesis". A winter rainfall drying between 4.2 and 3.9 kyr BP was followed by a summer rainfall drying between 3.97 kyr BP and at least 3.4 kyr BP. The Double Drying hypothesis provides more detailed climatic context for the Harappan civilization, resolves the cropping paradox, and fits the spatial-temporal pattern of urban abandonment. The consequences for the new Mid- to Late-Holocene Global Boundary Stratotype Section and Point in a stalagmite from Meghalaya are explored. Graphical abstract: Image 1 Highlights: Monte-Carlo principal component analysis of ten high resolution paleoclimate records. The dominant mode of climate variability is a drying beginning at 3.97 kyr BP. The 4.2 ka event can be locally significant but is not regionally coherent. Double Drying hypothesis details consecutive winter and summer dryings in the Indus valley. Hypothesis resolves cropping paradox and fits spatial pattern of Harappan site abandonment.